Analysis of conserved miRNAs in cynomolgus macaque genome using small RNA sequencing and homology searching - Xia Huang; Shijia Li; Xiaoming Liu; Shuting Huang; Shuang Li; Min Zhuo (PeerJ, 2020)
MicroRNAs (miRNAs) are important regulators that fine-tune diverse cellular activities. Cynomolgus macaques (Macaca fascicularis) are used extensively in biomedical and pharmaceutical research; however, substantially fewer miRNAs have been identified in this species than in humans. Consequently, we investigated conserved miRNA profiles in cynomolgus macaques by homology searching and small RNA sequencing. In total, 1,455 high-confidence miRNA gene loci were identified, 408 of which were also confirmed by RNA sequencing, including 73 new miRNA loci reported in cynomolgus macaques for the first time. Comparing miRNA expression with age, we found a positive correlation between sequence conservation and expression levels during miRNA evolution. Additionally, we found that the miRNA gene locations in cynomolgus macaque genome were very flexible. Most were embedded in intergenic spaces or introns and clustered together. Several miRNAs were found in certain gene locations, including 64 exon-resident miRNAs, six splice-site-overlapping miRNAs (SO-miRNAs), and two pairs of distinct mirror miRNAs. We also identified 78 miRNA clusters, 68 of which were conserved in the human genome, including 10 large miRNA clusters predicted to regulate diverse developmental and cellular processes in cynomolgus macaque. Thus, this study not only expands the number of identified miRNAs in cynomolgus macaques but also provides clues for future research on the differences in miRNA repertoire between macaques and humans.